Frequency of takotsubo cardiomyopathy in epilepsy-related hospitalizations among adults and its impact on in-hospital outcomes: A national standpoint. (15th January 2020) - Desai, Rupak; Singh, Sandeep; Patel, Upenkumar; Fong, Hee Kong; Kaur, Vikram Preet; Varma, Yash; Madan, Dyutima; Patel, Smit; Mahuwala, Zabeen; Sachdeva, Rajesh; Kumar, Gautam
Abstract: Background: Literature remains constrained to case reports with respect to epilepsy-associated takotsubo cardiomyopathy (TC) or stress-induced cardiomyopathy and its impact on in-hospital outcomes remains largely obscure. Methods: The National Inpatient Sample databases (2010–2014) were queried to identify and compare baseline characteristics and outcomes in adult hospitalizations for epilepsy with and without secondary TC using ICD-9-CM codes and propensity-matching. Primary outcomes were the frequency of TC, ensuing all-cause mortality, and complications. Secondary outcome was healthcare resource utilization. Results: Of 981, 571 epilepsy-related hospitalizations, 854 (0.1%, 1 in 1000) admissions (unspecified, 49.1%; grand mal/status epilepticus, 28.1% and generalized convulsive 11.7%) revealed associated in-hospital TC. Of the propensity-matched cohorts of epilepsy (TC = 793; mean 61.1 ± 15.0 yrs. & 82.4% females vs. non-TC = 795; mean 60.7 ± 14.2 yrs. & 84.2% females), the TC group consisted more often white (83.7% vs. 78.0%, p  < 0.02) patients with higher cardiovascular risk factors. The all-cause inpatient mortality (3.7% vs <11; p  = 0.002), arrhythmia (22.7% vs. 18.7%, p  = 0.05), cardiac arrest (3.9% vs <11; p  = 0.001), cardiogenic shock (3.2% vs <11, p  < 0.001), stroke (3.5% vs 1.9%, p  = 0.04), venous thromboembolism (4.4% vs. 1.9%, p  = 0.004), and respiratory failure (29.4% vs. 14.8%, p  < 0.001) were significantly higher in the TC cohort. The mean LOS (6.3 ± 5.6 vs. 5.1 ± 7.1 days), hospital charges ($77, 908 vs. $45, 881), transfers to other facilities (3.8% vs. 3.2%), and need of home healthcare (19.4% vs. 9.9%) were higher in the TC group ( p  < 0.001). Conclusion: In this nationwide population-based study, 1 in every 1000 epilepsy-related hospitalizations was associated with secondary TC which resulted in poor inpatient outcomes and higher healthcare resource utilization. Highlights: Of 981, 571 epilepsy admissions, 854 (0.1%/1:1000) revealed secondary in-hospital TC. Propensity-matched epilepsy-TC cohort (mean 61 yrs) consisted often white female patients. Propensity-matched TC cohort showed higher cardiac risk factors compared to non-TC cohort. The occurrence of TC increased all-cause mortality, complications, and resource utilization. Epilepsy-TC cohort had higher length of stay and hospital charges as compared to non-TC group.